# Table of Integrals - Forms Involving Inverse Hyperbolic Functions

The integrals below involve inverse hyperbolic functions.

1) int  sinh^-1(x/a)  dx = x sinh^-1(x/a)-sqrt(x^2+a^2)

2) int  x*sinh^-1(x/a)  dx = (x^2/2+a^2/4)sinh^-1(x/a)-(xsqrt(x^2+a^2))/4

3) int  x^2  sinh^-1(x/a)  dx = x^3/3sinh^-1(x/a)+((2a^2-x^2)sqrt(x^2+a^2))/9

4) int  (sinh^-1(x/a))/x  dx = x/a-(x/a)^3/(2*3*3)+(1*3(x/a)^5)/(2*4*5*5)-(1*3*5(x/a)^7)/(2*4*6*7*7)+...                     **[For absx < a]

OR = (ln^2((2x)/a))/2-(a/x)^2/(2*2*2)+(1*3(a/x)^4)/(2*4*4*4)-(1*3*5(a/x)^6)/(2*4*6*6*6)+...           **[For x > a]

OR =-(ln^2((-2x)/a))/2+(a/x)^2/(2*2*2)-(1*3(a/x)^4)/(2*4*4*4)+(1*3*5(a/x)^6)/(2*4*6*6*6)-...    **[For x < -a]

5) int  (sinh^-1(x/a))/x^2  dx = -(sinh^-1(x/a))/x-1/a ln((a+sqrt(x^2+a^2))/x)

6) int  cosh^-1(x/a)  dx = x*cosh^-1(x/a)-sqrt(x^2-a^2)                    **[For cosh^-1(x/a) > 0]

OR =x*cosh^-1(x/a)+sqrt(x^2-a^2)                    **[For cosh^-1(x/a) < 0]

7) int  x*cosh^-1(x/a)  dx = 1/4(2x^2-a^2) cosh^-1(x/a)-1/4 x sqrt(x^2-a^2)                    **[For cosh^-1(x/a) > 0]

OR =1/4(2x^2-a^2) cosh^-1(x/a)+1/4 x sqrt(x^2-a^2)                     **[For cosh^-1(x/a) < 0]

8) int  x^2 cosh^-1(x/a)  dx = 1/3x^3cosh^-1(x/a)-1/9(x^2+2a^2)sqrt(x^2-a^2)                    **[For cosh^-1(x/a) > 0]

OR = 1/3x^3cosh^-1(x/a)+1/9(x^2+2a^2)sqrt(x^2-a^2)                    **[For cosh^-1(x/a) < 0]

9) int  (cosh^-1(x/a))/x  dx = +-[1/2 ln^2((2x)/a)+(a/x)^2/(2*2*2)+(1*3(a/x)^4)/(2*4*4*4)+(1*3*5(a/x)^6)/(2*4*6*6*6)+...]

**[+ if cosh^-1(x/a) > 0; - if cosh^-1(x/a) < 0]

10) int  (cosh^-1(x/a))/x^2  dx = -(cosh^-1(x/a))/x+-1/a ln ((a+sqrt(x^2+a^2))/x)

**[+ if cosh^-1(x/a) < 0; - if cosh^-1(x/a) > 0]

11) int  tanh^-1(x/a)  dx = x*tanh^-1(x/a)+a/2 ln (a^2-x^2)

12) int  x*tanh^-1(x/a)  dx = (ax)/2+1/2(x^2-a^2)tanh^-1(x/a)

13) int  x^2tanh^-1(x/a)  dx = (ax^2)/6+x^3/3 tanh^-1(x/a)+a^3/6 ln (a^2-x^2)

14) int  (tanh^-1(x/a))/x  dx = x/a+(x/a)^3/3^2+(x/a)^5/5^2+...

15) int  (tanh^-1(x/a))/x^2  dx = -(tanh^-1(x/a))/x+1/(2a) ln (x^2/(a^2-x^2))

16) int  coth^-1(x/a)  dx = x*coth^-1x+a/2 ln(x^2-a^2)

17) int  x*coth^-1(x/a)  dx = (ax)/2+1/2(x^2-a^2)coth^-1(x/a)

18) int  x^2coth^-1(x/a)  dx = (ax^2)/6+x^3/3coth^-1(x/a)+a^3/6 ln (x^2-a^2)

19) int  (coth^-1(x/a))/x  dx = -(a/x+(a/x)^3/3^2+(a/x)^5/5^2+...)

20) int  (coth^-1(x/a))/x^2  dx = -(coth^-1(x/a))/x+1/(2a) ln (x^2/(x^2-a^2))

21) int  sech^-1(x/a)  dx = x*sech^-1(x/a)+a sin^-1(x/a)     **[For sech^-1(x/a) > 0]

OR = x*sech^-1(x/a)-a sin^-1(x/a)     **[For sech^-1(x/a) < 0]

22) int  x*sech^-1(x/a)  dx = 1/2x^2sech^-1(x/a)-1/2asqrt(a^2-x^2)     **[For sech^-1(x/a) > 0]

OR = 1/2x^2sech^-1(x/a)+1/2asqrt(a^2-x^2)     **[For sech^-1(x/a) < 0]

23) int  (sech^-1(x/a))/x  dx = -1/2 ln(a/x) ln((4a)/x)-(x/a)^2/(2*2*2)-(1*3(x/a)^4)/(2*4*4*4)-...     **[For sech^-1(x/a) > 0]

OR =  1/2 ln(a/x) ln((4a)/x)+(x/a)^2/(2*2*2)+(1*3(x/a)^4)/(2*4*4*4)+...         **[For sech^-1(x/a) < 0]

24) int  csch^-1(x/a)  dx = x*csch^-1(x/a)+-a sinh^-1(x/a)     **[+ if x > 0; - if x < 0]

25) int  x*csch^-1(x/a)  dx = x^2/2csch^-1(x/a)+-(asqrt(x^2+a^2))/2     **[+ if x > 0; - if x < 0]

26) int  (csch^-1(x/a))/x  dx = 1/2 ln(x/a) ln((4a)/x)+(1(x/a)^2)/(2*2*2)-(1*3(x/a)^4)/(2*4*4*4)+...     **[For 0 < x < a]

OR = 1/2 ln(-x/a) ln(-x/(4a))-(x/a)^2/(2*2*2)+(1*3(x/a)^4)/(2*4*4*4)+...     **[For -a < x < 0]

OR = -a/x+(a/x)^3/(2*3*3)-(1*3(a/x)^5)/(2*4*5*5)+...     **[For absx > a]

27) int  x^m sinh^-1(x/a)  dx = x^(m+1)/(m+1)sinh^-1(x/a)-1/(m+1) int  x^(m+1)/sqrt(x^2+a^2)  dx

28) int  x^m cosh^-1(x/a)  dx = x^(m+1)/(m+1) cosh^-1(x/a)-1/(m+1) int  x^(m+1)/sqrt(x^2-a^2)  dx     **[For cosh^-1(x/a) > 0]

OR = x^(m+1)/(m+1) cosh^-1(x/a)+1/(m+1) int  x^(m+1)/sqrt(x^2-a^2)  dx      **[For cosh^-1(x/a) < 0]

29) int  x^m tanh^-1(x/a)  dx = x^(m+1)/(m+1) tanh^-1(x/a)-a/(m+1) int  x^(m+1)/(a^2-x^2)  dx

30) int  x^m coth^-1(x/a)  dx = x^(m+1)/(m+1) coth^-1(x/a)-a/(m+1) int  x^(m+1)/(a^2-x^2)  dx

31) int  x^m sech^-1(x/a)  dx = x^(m+1)/(m+1) sech^-1(x/a)+a/(m+1) int  x^m/sqrt(a^2-x^2)  dx     **[For sech^-1(x/a) > 0]

OR = x^(m+1)/(m+1) sech^-1(x/a)-a/(m+1) int  x^m/sqrt(a^2-x^2)  dx     **[For sech^-1(x/a) < 0]

32) int  x^m csch^-1(x/a)  dx = x^(m+1)/(m+1) csch^-1(x/a) +- a/(m+1) int  x^m/sqrt(x^2+a^2)  dx     **[+ if x > 0; - if x < 0]